As chamas da fé: a ação da Liga Católica contra o protestantismo no campo religioso recifense (1902-1910). - Menezes, Evily Lima (2024)
The Brazil of the 19th century went through several changes, and religion was one of the areas that was notably altered. The Catholic institution was the only religious guide in the socio-political formation of the Portuguese colony, thus generating a great impasse with the arrival of other Christian churches in the country, thanks to the small liberations of the 1824 Constitution. When the Republic coup occurred in 1889, and consequently in January 1890, the secular state was officially established in article 119-A. The legal freedom given to religions led to a more emphatic reaction from the Brazilian episcopate, already imbued with the First Vatican Council (1869-70) and subsequent papal encyclicals. A Catholic reaction was established, with the publication of pastoral letters and diocesan Catholic congresses. These actions targeted various areas, such as the press, education, festivals, missions, and the fight against Protestantism. This work is dedicated to studying the Catholic reaction in the capital of Pernambuco at the beginning of the 20th century, after the Pernambuco Catholic Congress of 1902. Pernambuco is the only state in the country that organizes an official body against Protestantism, named "League against Protestantism," founded in September of the same year, based at Our Lady of Penha Church in the São José neighborhood of Recife. The League regularly published in the main circulating newspapers of Recife, especially in A Província: órgão do Partido Liberal. The publications addressed key pillars of the Catholic faith to reach believers and shield them from Protestant heresies. The league gained prominence in its period for its manifestation of its fight through burning Protestant Bibles inciting debates about religious limits and tolerance. We will use sociologist Pierre Bourdieu's view on methods for maintaining the Roman Church and the struggle for dominance in the religious field in Recife, understanding the League both as an action and as a reaction to the religious and ideological conjecture of that time.